Studi Ekologi dan Pemanfaatan Tumbuhan Famili Solanaceae di Kecamatan Tugumulyo - Yuli Febrianti; Yuni Krisnawati (Biota, 2018)
The purpose of this study is to determine the ecological factors in the growth site of the Solanaceae family and the plant species of the Solanaceae family that can and can not be consumed in Tugumulyo District.The type of this research is descriptive exploration. Technique of taking data with observation and interview. The work done is direct observation to the field. Data obtained from the research are analyzed descriptively qualitative. The result of this research is ecological factor at the growth site of Solanaceae family in Tugumulyo District ranges between temperature 27-33oC, humidity is 69 - 92%, and acidity degree (pH) 6,2 - 6,8. A total of 9 species that can be consumed and made into spices and vegetables are Capsicum annum, Capsicum, frutescens, Physalis angulata, Solanum indicum, Solanum lycopersicum, Solanum melongena, Solanum nigrum, Solanum torvum, Solanum tuberosum. And 2 species that can not be consumed by the public and toxic are Cestrum nocturnum and Datura metel which is an ornamental plant.